2017
DOI: 10.1042/cs20171256
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic effect of a novel Wnt pathway inhibitor on cardiac regeneration after myocardial infarction

Abstract: After myocardial infarction (MI), the heart is difficult to repair because of great loss of cardiomyoctyes and lack of cardiac regeneration. Novel drug candidates that aim at reducing pathological remodeling and stimulating cardiac regeneration are highly desirable. In the present study, we identified if and how a novel porcupine inhibitor CGX1321 influenced MI and cardiac regeneration. Permanent ligation of left anterior descending (LAD) coronary artery was performed in mice to induce MI injury. Cardiac funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 41 publications
1
43
1
1
Order By: Relevance
“…The authors conclude, however, that an antifibrotic effect involving collagen-VI was responsible for the beneficial effect on infarct healing of WNT-974. In contrast to the studies with Porcupine inhibitors mentioned above, Yang et al (2017) demonstrated not only reduced infarct size and improved function but also a significant increase in newly formed CMs in the border zone of mice treated with the Porcupine inhibitor CGX1321 for 4 weeks post-MI. The total number of 5-ethynyl-29-deoxyuridine (EdU)positive mononucleated adult CMs was found to be significantly up-regulated, which was indicative for induction of CM proliferation by the Porcupine inhibitor.…”
Section: Wnt Signalingcontrasting
confidence: 86%
“…The authors conclude, however, that an antifibrotic effect involving collagen-VI was responsible for the beneficial effect on infarct healing of WNT-974. In contrast to the studies with Porcupine inhibitors mentioned above, Yang et al (2017) demonstrated not only reduced infarct size and improved function but also a significant increase in newly formed CMs in the border zone of mice treated with the Porcupine inhibitor CGX1321 for 4 weeks post-MI. The total number of 5-ethynyl-29-deoxyuridine (EdU)positive mononucleated adult CMs was found to be significantly up-regulated, which was indicative for induction of CM proliferation by the Porcupine inhibitor.…”
Section: Wnt Signalingcontrasting
confidence: 86%
“…While studies employing cultured rat cardiomyocytes and embryonic mice have demonstrated that Wnt/β-catenin signaling is a positive regulator of cardiomyocyte proliferation in the absence of insult ( Buikema et al, 2013 ; Heallen et al, 2011 ; Ozhan and Weidinger, 2015 ; Tseng et al, 2006 ; Ye et al, 2015 ), our data have uncovered an injury-dependent inhibitory role during zebrafish heart regeneration. This function is likely to be conserved in mammals as inhibition of Wnt signaling following experimental myocardial infarction in mice stimulated cardiomyocyte proliferation and improved outcomes ( Bastakoty et al, 2016 ; Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signalling is known to exert a crucial function in heart development and CM specification . Yet, the roles of this pathway on heart regeneration are still poorly understood , and current evidence appears to indicate that inhibition of this pathway promotes CM proliferation during zebrafish regeneration and in infarcted mice .…”
Section: The Microtubular Network At the Interface Between Mechanosenmentioning
confidence: 99%